Urinothorax: A Rare Postoperative Complication of Adrenalectomy - Puthenveedu, Deepa Kalikavil (J Clin Diagn Res, 2016)
Urinothorax is a rare condition defined by the presence of urine in the pleural cavity. Here we report a case of a patient with left sided transudative pleural effusion which developed following left adrenalectomy with perisplenic collection. The pleural fluid to serum creatinine ratio was found to be greater than one which confirmed the diagnosis. The objective of this case report was to describe this rare case and to alert the physicians to include urinothorax in their differential diagnosis of transudative pleural effusion especially following abdominal surgery.